2020
DOI: 10.1002/syn.22147
|View full text |Cite
|
Sign up to set email alerts
|

5ʹUTR polymorphism in the serotonergic receptor HTR3A gene is differently associated with striatal Dopamine D2/D3 receptor availability in the right putamen in Fibromyalgia patients and healthy controls—Preliminary evidence

Abstract: Background Extensive literature has investigated the role of serotonin (5‐HT) in the control of the central dopamine (DA) systems, and their dysfunction in the pathological conditions. 5‐HT stimulates the local DA release in striatal regions via activation of various receptors including serotonin receptor‐3 (5‐HT3). Several studies have related polymorphisms (SNPs) in the serotonin receptor‐3 (HTR3) genes to be associated with the pain modulation and endogenous pain suppression. A few studies suggested a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
(97 reference statements)
0
3
0
1
Order By: Relevance
“…Some researchers demonstrated that the loss of the HTR3A gene or HTR3A inactivation can induce anxiolytic-like features that have comparability of 5-HT 3 antagonists [ 34 ]. More interestingly, anxiety disorder and pain share the same pathway that gives us more chance to focus on the polymorphism of the HTR3A gene to manage chronic pain [ 31 , 35 , 36 ]. DRD2 is also a risk gene related to GAD and may predict mental disorders at an early age [ 37 , 38 ].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Some researchers demonstrated that the loss of the HTR3A gene or HTR3A inactivation can induce anxiolytic-like features that have comparability of 5-HT 3 antagonists [ 34 ]. More interestingly, anxiety disorder and pain share the same pathway that gives us more chance to focus on the polymorphism of the HTR3A gene to manage chronic pain [ 31 , 35 , 36 ]. DRD2 is also a risk gene related to GAD and may predict mental disorders at an early age [ 37 , 38 ].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Carriers of the CC genotype were found to have fewer dopamine receptors available when compared to TT carriers, suggesting that CC carriers may experience less reward associated with dopamine release. However, there was no association between rs1062613 and pain threshold or tolerance [ 54 , 55 ]. Further examination of six different 5-HTR3a variants and eight different 5-HTR3b variants revealed mixed results when compared to healthy controls [ 55 ].…”
Section: Genetic Contributions To the Development Of Fmmentioning
confidence: 99%
“…Moreover, the 11 C-raclopride PET bolus-plus-infusion method was used to measure the 11 C-raclopride receptor binding potential between an unpredictable reward condition and a sensorimotor control condition, with the aim to investigate the role of serotonin (5-HT) in the control of central dopamine systems, and their dysfunction in FM patients, suggesting a potential role of serotonin polymorphism in DA receptor modulation [ 39 ]. Furthermore, 18 F-fallypride (FAL) is a further example of a suitable PET compound for the investigation of extrapyramidal D(2)-receptors, also bonding to D(2)-receptor sites, as shown by the preclinical findings [ 68 ].…”
Section: Novel Imaging Approaches To Fibromyalgiamentioning
confidence: 99%